DEPRESSIVE FEELINGS OF ELDERLY CLIENTS ABOVE THE AGE OF 60 YEARS LIVING WITH THEIR FAMILY MEMBERS - Daflary Nani (Indian Journal of Psychiatric Nursing)
It is an explorative survey study to assess the depressive feelings experienced by 160 elderly clients above the age of 60 years living with their family members and its associated causative factors in selected villages of Dhemaji district, Assam. Major findings of the study revealed that the majority of the respondents were between the age group of 60-70 years (49.4 %), male (58.1), married (64.4%), belongs to joint family system (74.4), illiterate (45.6%), depends mainly on cultivation and other sort of business (61.9%). The mean depression score was 19.73±7.17 indicating negative skewness of −0.90 a total of 86.9% elderly were screened as depression whereas 25% of them were mildly depressed and 61.9% of them were severely depressed. Most frequently reported individual causative factors associated with elderly depression are economical problem (73.8%) which is followed by chronic pain (65.6%), loneliness (62.5%), lack of time spent of the children with elderly (61.3%), lack of involvement in work (55%) Geriatric Score has revealed no association with individual and familial cause while it is significantly correlated to social cause.